Incorporation of Ion Post Stripper in the APAPES Experimental Setup - Asimakopoulou, E. M.; Madesis, I.; Zouros, T. J. M.; Mertzimekis, T. J.; Lagoyannis, A.; Axiotis, M. (HNPS Advances in Nuclear Physics, 2019)
A new accelerator beam line dedicated to atomic collision physics has been constructed as part of the APAPES project that is being carried out at the TANDEM of the NCSR “Demokritos”. Interest in various charge states resulted in the design of a second stripping point after acceleration that was added to the main part of the TANDEM accelerator after the analyzing magnet. In addition, the charge-state analysis program named TARDIS was implemented in C# code to assist in the optimal charge selection.